A Framework for Research in Transition: Identifying Important Areas and Intersections for Future Study. (February 2020) - Trainor, Audrey A.; Carter, Erik W.; Karpur, Arun; Martin, James E.; Mazzotti, Valerie L.; Morningstar, Mary E.; Newman, Lynn; Rojewski, Jay W.
The role of research in transition education has been prominent and influential. Yet too many young people with disabilities are still not experiencing outcomes aligned with their personal aspirations and priorities. Moreover, individuals with disabilities continue to experience barriers to employment, educational, economic, and other challenges well into adulthood. Moving forward as a field will require continued investment in strong scholarship and careful consideration of new areas of inquiry. In this article, we present a framework for transition research designed to identify key issues and intersections in which future inquiry should be directed. We present research needs in six different areas to illustrate these possibilities. We also highlight some of the complexities and considerations associated with conducting this research.